DETERMINANT CURRENT RATIO AND DEBT TO EQUITY RATIO IN ASSESSING FINANCIAL PERFORMANCE - Firman, Dody; Aslam, Ahmad (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
This study aims to determine the financial performance of PT. Mestika Sakti Medan which is measured using the liquidity ratio (current ratio), solvency ratio (Debt to Equity Ratio).This study uses a descriptive approach, with the types of research data in the form of quantitative data anddata source, namely primary data. The data collection technique used is documentation and tThe data analysis technique used is descriptive analysis. The results showed that the financial performance of PT. Mestika Sakti Medan which was analyzed using the Carrent Ratio and Debt to Equity Ratio based on the 2009-2018 financial statements, namelyit can be seen that the current ratio is stable on average but if measured by industry standards it is below the industry standard, the Debt to Equity Ratio on average has increased and when compared to industry standards it has increased. This can be seen from the large number of current assets compared to current liabilities, the increase in total assets, the decrease in the company's ability to generate profits and the company's ability to pay all company obligations.